(untitled) (The Research of Medical Science Review, 2025)
Background Pregnancy induces significant physiological and psychological changes, often leading to elevated stress, anxiety, and depression. This study aimed to compare physical and mental health parameters between pregnant and non-pregnant women to identify disparities and guide targeted interventions. Methods A cross-sectional study was conducted on 200 participants (100 pregnant, 100 non-pregnant) recruited from a healthcare institution in Hyderabad, Pakistan. Physical health parameters, including BMI, blood pressure, and waist-hip ratio, were measured. Mental health was assessed using validated scales for stress, anxiety, and depression. Data were analyzed using descriptive statistics, independent t-tests, and correlation analyses. Results Pregnant women exhibited higher BMI (29.5 ± 3.0 vs. 23.8 ± 2.5, p < 0.0001), systolic blood pressure (125 ± 7.5 mmHg vs. 115 ± 7.0 mmHg, p < 0.0001), and waist-hip ratio (0.95 ± 0.07 vs. 0.82 ± 0.06, p < 0.0001) compared to non-pregnant women. Mental health scores were also significantly elevated in the pregnant group, with stress (3.5 ± 0.8 vs. 1.5 ± 0.6, p < 0.0001), anxiety (3.4 ± 0.9 vs. 1.4 ± 0.5, p < 0.0001), and depression (3.3 ± 0.9 vs. 1.3 ± 0.6, p < 0.0001). Correlations were observed between BMI and blood pressure (r = 0.76, p < 0.0001) and between stress, anxiety, and depression (r > 0.80, p < 0.0001). Conclusion Pregnant women exhibited significantly higher BMI, blood pressure, and mental health distress compared to non-pregnant women. The findings highlight the need for integrating routine mental health screenings and targeted interventions in antenatal care. Future longitudinal research should explore the persistence of these disparities postpartum.